Differential quadrature modeling of laminated composite in a three-dimensional layerwise framework - Zhang, Zheng. (2008)
The objectives of this project are twofold: (1) Development of the differential quadrature (DQ) method for applications to laminated composites; and (2) Explore new modeling techniques to examine the behaviors of thick laminated composites.